Assistance in Learning English Tenses (Simple Present, Continuous, Simple Past) and Prepositions through a Community Service Program by English Education Students for Junior High School Students of Grades VII-VIII - Abdul Syahid; Marshanda Marshanda; Muhammad Alief Raihan Ramadhan; Raysha Ramadhani; Syarifah Soraya; Rani Rani; Najwa Amalia; Najwa Rizki Amalia; Muhammad Dicky Setiawan; Yasmine Mumtaazah; Ciraenda Caenovea (English Education and Literature Journal (E-Jou), 2026)
This community service initiative was carried out by English Education students from the Faculty of Tarbiyah and Teacher Training at State Islamic University of Palangka Raya. The program aimed to enhance junior high school students’ understanding of key English grammar components—specifically the simple present, present continuous, and simple past tenses, as well as the correct use of prepositions. Conducted over two days, the program involved structured lessons using school-provided textbooks, visual aids, and interactive activities such as grammar games and group discussions. Data were collected through direct observation, Q&A sessions, and practice exercises to evaluate students' comprehension and application of the material. The findings indicate that the use of contextualized instruction, real-life examples, and communicative activities—supported by visual media and practice exercises—effectively improved students' grammatical accuracy, confidence, and engagement. The involvement of English education university students as peer facilitators fostered a more interactive and less intimidating learning environment. This program also reinforced the pedagogical value of experiential learning, benefiting both junior high school students and pre-service teachers by providing meaningful and reflective teaching experiences aligned with real classroom needs. Overall, this initiative successfully addressed students’ learning gaps in English grammar and showcased the benefits of integrating community service into teacher education